Environmental practices used in buffalo milk production: an overview of studies - Soares, Bruna Borges; Maranduba , Henrique Leonardo; Rodrigues, Luciano Brito (Brazilian Journal of Production Engineering, 2024)
Buffalo is the main supplier of milk in several countries. Due to the growing demand for food, the production and consumption of buffalo milk, as well as its dairy derivatives, have driven the exploration of this activity worldwide. However, the environmental impacts resulting from the activity are undeniable and have driven the search for more sustainable production methods and directed efforts in this direction. The study in question carried out a survey of work related to environmental practices used in buffalo production. A preliminary survey identified 463 studies for the keywords used, of which only 8% contained an environmental approach, including the Life Cycle Assessment (LCA) methodology, key tools for assessing environmental sustainability. The identified works evaluated, in addition to GHG emissions and their association with global warming potential, other impacts, such as abiotic depletion, acidification and eutrophication of waters. The results found demonstrate the contemporary nature of the topic. However, it is worth highlighting that there have been few studies carried out so far and, therefore, it is an opportune field of study for development of research, as sustainable measures are increasingly required in the various agricultural segments.
Keywords: Environmental Impacts; Environmental management; Life Cycle Assessment; Sustainability